Diaphragm thickness, thickness change, and excursion in subjects with and without nonspecific low back pain using B-mode and M-mode ultrasonography. - Ziaeifar, Maryam; Sarrafzadeh, Javad; Noorizadeh Dehkordi, Shohreh; Arab, Amir Massoud; Haghighatkhah, Hamidreza; Zendehdel Jadehkenari, Alieh (Physiotherapy Theory & Practice, 2022)
Previous studies have demonstrated that respiratory dysfunction has a potential association with low back pain (LBP). Despite the role of the diaphragm for respiration and spinal stability, knowledge of the function of both sides of the diaphragm in subjects with LBP is still limited. This study aimed to compare the structural integrity and function of the right and left hemidiaphragm by ultrasonography (USG) in subjects with and without nonspecific chronic low back pain (NS-CLBP). A total of 37 subjects with NS-CLBP and 34 healthy subjects participated in this case-control study. The thickness, thickness change, and excursion of the right and left hemidiaphragm were compared within and between the groups during quiet breathing (QB) and deep breathing (DB) through B-mode and M-mode ultrasound imaging. The LBP group had a significantly smaller degree of right hemidiaphragm thickness change (P =.001) compared with the healthy control group, with a strong effect size. Nevertheless, there was no significant change for diaphragm thickness and excursion between the two groups. The result showed that, in the healthy group, the right hemidiaphragm had a significantly smaller thickness at expiration and larger thickness change compared with the left hemidiaphragm, with a moderate effect size. Based on the multivariate prediction analysis, the right hemidiaphragm thickness change might significantly predict LBP. We found that participants with LBP had a smaller degree of right hemidiaphragm thickness change. Also, the right hemidiaphragm thickness change might significantly predict LBP.